Monitoring food and non‐alcoholic beverage promotions to children. (17th September 2013) - Kelly, B.; King, L.; Baur, L.; Rayner, M.; Lobstein, T.; Monteiro, C.; Macmullan, J.; Mohan, S.; Barquera, S.; Friel, S.; Hawkes, C.; Kumanyika, S.; et al.
Summary: Food and non‐alcoholic beverage marketing is recognized as an important factor influencing food choices related to non‐communicable diseases. The monitoring of populations' exposure to food and non‐alcoholic beverage promotions, and the content of these promotions, is necessary to generate evidence to understand the extent of the problem, and to determine appropriate and effective policy responses. A review of studies measuring the nature and extent of exposure to food promotions was conducted to identify approaches to monitoring food promotions via dominant media platforms. A step‐wise approach, comprising 'minimal', 'expanded' and 'optimal' monitoring activities, was designed. This approach can be used to assess the frequency and level of exposure of population groups (especially children) to food promotions, the persuasive power of techniques used in promotional communications (power of promotions) and the nutritional composition of promoted food products. Detailed procedures for data sampling, data collection and data analysis for a range of media types are presented, as well as quantifiable measurement indicators for assessing exposure to and power of food and non‐alcoholic beverage promotions. The proposed framework supports the development of a consistent system for monitoring food and non‐alcoholic beverage promotions for comparison between countries and over time.